Predicting pronasale position in Thais: a test of four updated methods - Sumon Thitiorul (2020)
© 2019, © 2019 Australian Academy of Forensic Sciences. The methods for pronasale prediction proposed by Stephan et al. (2003), Rynn et al. (2010), Lee et al. (2014) and Utsuno et al. (2016) were tested in order to find applicable methods for a Thai population. Cone-beam computed tomography data from 100 adult subjects were analysed, using two- and three-dimensional images. The data were categorized into females, males and regardless of sex groups. Differences between the predicted and actual coordinates were compared using the paired t-test and mean absolute errors (MAEs). Differences between each prediction methods were compared using the two-way ANOVA with a balanced block design or Friedman tests. Our results suggest that the preferable methods for pronasale prediction in the female and male groups are the methods of Utsuno et al. and Lee et al, respectively. The mean and MAE for pronasale projection and height, calculated by the method of Utsuno et al. in females were 0.4(1.9) and −0.4 (1.5) mm. Those value calculated by the method of Lee et al. in males were −0.7(1.9), 1.0 (1.9) mm. Our result can help to select the suitable prediction methods applying for nasal tip prediction for facial reconstruction in a Thai population.